Economic Implications of Senior High School to Parents in Southern Philippines: A Rural-Urban Perspective - Basaluddin, Kadafi A. (Open Access Indonesia Journal of Social Sciences, 2021)
This pioneer study unravelled the economic implications of Senior High School (SHS) curriculum to parents in the rural area of Jolo and the urban center of Zamboanga City. Finding out the significant difference of said implications to parents clustered according to: Area Status, and Children’s Grade Level and Children’s School Type, and SHS-Associated Factors causing financial difficulty to them in both areas are also within the confine of this endeavour. As an expose facto cross-sectoral and evaluative survey, this research employed a qualitative descriptive approach. One hundred twenty seven (127) respondents comprising of parents and senior high principals/coordinators/directors were determined through a Purposive sampling method. Weighted Mean, t-test (Independent Sample-Test), and Ordinal Scales were utilized in analysing the data. The findings are forwarded - The economic implications of the curriculum to parents in both areas are as follows: more spending for school and non-school needs of children, compromised other household expenses and needs of the family, difficulty to support the education of senior high and non-senior high children, compromised expenses on non- senior high children, increased in educational expenses, costly secondary education, increased of daily expenses, financial burden, difficulty to manage income, difficulty to deal with tuition and miscellaneous fees, difficulty to save money, compromised personal and social expenses, need to generate extra income and borrow money to support the education of children, difficulty to extend financially assistance to needy relatives and friends (rural respondents), and difficulty to attend to social obligations on regular basis (rural respondents). As to the extent/intensity of the implications, parents in SCT-SHS and NDJC-SHS in rural area are more affected by the curriculum than the rest. While in urban center, parents in DPLMHS-SASHS and TTNHS-SHS are more affected than those in the four senior high schools. Generally, the extent/intensity of the economic implications of the curriculum to parents in both areas is slight. Income and tuition fee are among the top-ranking pre-determined SHS-Associated Factors causing financial difficulty to parents in rural area and urban center, and in the twelve senior high schools in both areas. Specifically, parents are shelling-out an average of PhP35,000 to 45,000 every year for the senior high education of their children. From the study findings, the researcher developed a model dubbed as Cycle of Despondency. The curriculum increases the private costs of education and burgles effluent family of two years of indispensable child’s contribution in terms of labor opportunity cost. Above all, it is taxing to parents beyond their financial capability to cope. Scrapping it, however, is indubitably not an astute plan. Instead, immediate and sweeping review and modification are prudent stratagems to undertake since it is already running for four years now. Program mitigating its pecuniary repercussions to parents have to be devised, along with inflexible regulation of school fees and charges. The Civil Service Commission (CSC) and corporate entities have to amend some job “educational requirements” to accommodate senior high graduates in the labor market. Studies on the economic aspect of the curriculum must be launched by various social divides - to spot genuine recommendations in aid of legislation and curriculum planning in general and map out alternative methodologies to minimize its impacts to family in particular. Otherwise, the curriculum will completely end up in fiasco.